Problem Analysis on Teachers in the Development of Discovery Learning Model-based Worksheet and Student Problem on Cognitive Learning Achievement - Panca Herlambang; Evi Palenewen; Susilo Susilo (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2018)
Abstract : The purpose of this research is to analyze the development of Biology worksheet about Blood Circulation System based on Discovery Learning model in SMA Negeri Samarinda. The research targets are (1) to describe the teacher's level of understanding about Discovery Learning model-based worksheet (2) to find solutions to solve teacher problem about worksheet development (3) to find out the level of student achievement (4) to find solutions regarding to low students’ learning achievement. The participants of this research are Biology teachers at SMAN 6, SMAN 14, SMAN 4 and SMAN 3 Samarinda. The results of this study were analyzed using qualitative descriptive methods. The results of this study indicate that (1) The teachers’ understanding about the development of Discovery Learning-based Biology worksheet is still inadequate so that worksheet application was not optimal in teaching and learning process. (2) The teachers still experience some difficulties in synthesising worksheet, thus teachers need more explanations and references in the development of Discovery Learning model-based worksheet. (3) The students’ learning achievement are not optimal, (4) Teachers’ guidance is the best solution to improve the students’ achievement.Key Words: Problem analysis, Worksheet, Discovery Learning, students’ achievement Abstrak : Penelitian ini bertujuan untuk melakukan analisis kebutuhan pengembangan LKS biologi pada materi sistem peredaran darah berbasis model Discovery Learning di SMA Negeri Samarinda. Target penelitian adalah untuk memperoleh (1) gambaran tingkat pemahaman guru terkait LKS berbasis model Discovery Learning (2) Solusi dalam mengatasi permasalahan guru terkait pengembangan LKS (3) tingkat pencapaian hasil belajar siswa .(4) solusi dalam mengatasi hasil belajar siswa. Populasi penelitian analisis kebutuhan ini adalah guru Biologi pada SMAN 6 ,SMAN 14, SMAN 4 ,dan SMAN 3 Samarinda. Hasil observasi permasalahan guru dan siswa yang di analisis secara deskriptif kualitatif menunjukkan bahwa (1) Pemahaman guru terkait pengembangan LKS biologi berbasis model Discovery Learning masih kurang sehingga penerapannya dalam kegiatan belajar mengajar tidak optimal. (2) Guru mengalami kendala dalam pembuatan LKS oleh karena itu guru memerlukan sosialisasi dan acuan referensi dalam pengembangan LKS berbasis model Discovery Learning dan (3) Hasil belajar siswa masuk kategori kurang, (4) Rendahnya hasil belajar siswa perlu diatasi dengan bimbingan dan pendampingan yang penuh oleh guru terkait hasil belajar siswa. Kata kunci : Analisis permasalahan , LKS, Discovery Learning, hasil belajar.